Ultrasonication Assisted Extraction of Lipids from Chlorella vulgaris with BmimMeSO4 as an Additive - Azman, N.S.B. (Springer Science and Business Media B.V., 2021)
Extraction of lipids using combination of methods with ultrasonic probe and ionic liquid were done towards the cultivated Chlorella vulgaris. In this research, BmimMeSO4 were synthesized by using alkylation and metathesis methods. Effect of methanol, time reaction and IL loading in extracting the lipids were investigated by using ultrasonication. Results indicate that, 40Â min gives the highest lipids extraction with 1.25% of BmimMeSO4 and methanol. Effect of temperature towards stirring methods were also studied in 40Â min duration. 23.81% lipids were extracted at 40Â Â°C as the optimum temperature. At room temperature, ultrasonication methods gave three times higher lipids extracted compared to stirring methods which are 26.78% and 9.25%, respectively. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.